2016
DOI: 10.3109/0886022x.2016.1160724
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress and its effects on renal tubular cells apoptosis in ischemic acute kidney injury

Abstract: Ischemia is the most frequent cause of acute kidney injury (AKI), which is characterized by apoptosis of renal tubular cell. A common result of ischemia in AKI is dysfunction of endoplasmic reticulum (ER), which causes the protein-folding capacity to lag behind the protein-folding load. The abundance of misfolded proteins stressed the ER and results in induction of the unfolded protein response (UPR). While the UPR is an adaptive response, over time it can result in apoptosis when cells are unable to recover q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 52 publications
3
36
0
Order By: Relevance
“…Here, our results suggested that impairment of autophagy induced by SUs might also contribute to the apoptosis of PTECs. In addition, our results are consistent with previous observations that autophagy protects PTECs from injury and apoptosis (Dong et al 2015; Xu et al 2016). Other research indicates that increased cytosolic Ca 2+ levels regulated by K ATP channels play a role in impairing autophagy, which is associated with neurodegenerative disorders (Hambrock et al 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Here, our results suggested that impairment of autophagy induced by SUs might also contribute to the apoptosis of PTECs. In addition, our results are consistent with previous observations that autophagy protects PTECs from injury and apoptosis (Dong et al 2015; Xu et al 2016). Other research indicates that increased cytosolic Ca 2+ levels regulated by K ATP channels play a role in impairing autophagy, which is associated with neurodegenerative disorders (Hambrock et al 2006).…”
Section: Discussionsupporting
confidence: 93%
“…When the balance breaks down within a variety of environmental insults including hypoxia, oxidative stress, and cell starvation, unfolded and malfolded proteins are unable to transport from ER lumen to other parts of cells or space out of cells and then loaded in the ER to trigger ER stress [9]. With the injury lasting long and progressing, ER stress known as prodeath pathway will result in apoptosis and other responses [10]. …”
Section: Introductionmentioning
confidence: 99%
“…In this study, we disclosed that apoptosis was the major mechanism contributing to the liver injury after transplantation [21-23]. Most importantly, UA pretreatment could alleviate the apoptosis [24]. There are a lot of studies confirmed the role of ERS in ischemia reperfusion injury after liver transplantation [25, 26]_ENREF_22_ENREF_1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also detected the expressions of apoptosis-related regulators. Caspase-3 is an apoptosis effector and the high level of caspase-3 indicates the increased apoptosis [24, 28]_ENREF_1. Although we also observed obvious apoptosis in UA treated group, this drug could increase the resistance of the transplanted livers.…”
Section: Discussionmentioning
confidence: 99%